Sikap Ilmiah Siswa Dalam Pembelajaran Fisika Dengan Penggunaan Media Komputer Melalui Model Kooperatif Tipe Stad Pada Siswa Kelas X3 Sma Negeri I Bangkinang Barat - Fakhruddin Z; Elva Eprina; Syahril Syahril (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2010)
This study aimed to describe student attitudes towards learning physics with computer media use through theimplementation of cooperative type STAD model in SMAN I X3 graders West Bangkinang 2009/2010academic year which amounts to 35 people with a sample of two groups totaling 12 people. Collecting databy using the observation sheet at each meeting. The technique of data analysis using descriptive analysis.Results of data analysis shows that on average during the three meetings have been 77.8% of students with ascientific high category, 19.4% of students have been scientifically medium category, and 2.7% of thestudents is still low in the scientific attitude. Thus the application of physics learning with computer mediause through the implementation of an effective model for cooperative type STAD X3 geade students at SMANI west Bangkinang subject matter of heat.